Polygenic risk score associates with atherosclerosis severity at autopsy. (3rd October 2022) - Cornelissen, A; Gadhoke, N V; Ryan, K; Hodonsky, C J; Duong, T V; Dikongue, A; Sakamoto, A; Sato, Y; Miller, C L; Hong, C C; Arking, D E; Mitchell, B D; et al.
Abstract: Background: Polygenic risk scores (PRS) for coronary artery disease (CAD) are emerging as a potential method to improve cardiovascular risk prediction. Questions remain about their applicability to diverse populations as well as their correlation with coronary histopathology. Purpose: To assess whether high genetic risk associates with histopathologic coronary plaque morphology. Methods: We assessed 122 known CAD risk loci in 954 Black and White subjects within our sudden death registry to generate a PRS. The cohort was divided into quintiles according to z-score-standardized PRS, both in a race-stratified fashion and in the pooled sample. Detailed histopathologic examination of the coronary arteries was performed in all subjects. Results: Subjects in the highest PRS quintile exhibited more severe atherosclerosis compared to subjects in the lowest quintile, with greater mean cross-sectional luminal narrowing (71.5% (95% CI, 66.6%-76.5%) vs. 56.6% (95% CI, 51.1%-62.1%); adjusted p<0.001; Figure 1) and a higher frequency of calcification (adjusted OR 2.19; 95% CI 1.31–3.68; p=0.003) after adjustment for the first 10 principal components, age, sex, and race. Higher z-score-standardized PRS was predictive for the finding of severe atherosclerosis (i.e., ≥75% cross-sectional luminal narrowing) even after additional controlling for traditional CAD risk factors including hypertension, smoking, diabetes mellitus, and hyperlipidemia (adjusted OR 1.39; 95% CI 1.19–1.63; p<0.001; Figure 2). Among Black subjects, higher PRS was associated with higher odds of plaque rupture (adjusted OR 1.31; 95% CI 1.03–1.66; p=0.03) and predicted CAD-associated cause of death among subjects younger than 50 years old (adjusted OR 1.26; 95% CI 1.01–1.58; p=0.04). Conclusions: This is the first autopsy study investigating associations between PRS and atherosclerotic plaque morphology at a histopathologic level. Our pathological analysis suggests PRS correlates with plaque burden and coronary artery calcification and may be useful as a method for CAD risk stratification, especially in younger subjects. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): R01 HL141425 Leducq Foundation Grant